A New Approach to Seasoning of Eucalyptus Hybrid (Eucalyptus teretlcornis) - Pandey, C. N.; Gaur, B. K.; Kanojia, H. C.; Chandra, Akash (Indian Forester, 1984)
Eucalypts being a highly refractory timber develop severe collapse, aurface cracks, warping and twisting during the process of air or kiln seasoning in tangentially sawn planks, which is a conventional and most commonly used proces. The adoption of radial sawing of eucalypt logs have shown that defect free planks can be obtained and can he subsequently seasoned also without cracking, collapse or warping defects. New seasoning schedules for seasoning of Eucolyptul planka of 25 mm thick have also been evaluated.